The Cyber Security Aspects in Founding a Social Media Influencing Based Company : When The Brand is You - Finska, Kia (My University, 2023)
Since the rise of social media, a new business field has been formed where content creators are selling their expertise, relationship with their followers, platform space and marketing space. Social media marketing has proven to be cost effective and a widely spread part of the new way of marketing – digital marketing. Social media influencers (SMIs) have used this change to grow their businesses and although it is still a rather new industry, it has grown into a popular marketing method where many SMIs are creating their careers in. Social media is a business platform for numerous social media influencers that are building their careers inside and with the use of popular applications. The cyber security issues specifically faced by these entrepreneurs have not been widely studied in literature. Usually discussed security measures in social media handle the issues of all users – private or not – leaving out the influencers and content creators that run a business on these platforms. Many current viruses, phishing attacks, cyber bullying, and other malicious online behavior is done through social media. Therefore, also content creators need to keep their security standards up to par, not only as social media users but as business owners. This thesis discusses the threats of social media for influencer businesses, the ways how a person can protect themselves and their businesses, and a hands-on framework for any influencer to adapt into their business and information technology usage.
Keywords: social media, cyber security, influencing, social media influencer, business